2019
DOI: 10.3390/nano9081089
|View full text |Cite
|
Sign up to set email alerts
|

Tangeretin-Assisted Platinum Nanoparticles Enhance the Apoptotic Properties of Doxorubicin: Combination Therapy for Osteosarcoma Treatment

Abstract: Osteosarcoma (OS) is the most common type of cancer and the most frequent malignant bone tumor in childhood and adolescence. Nanomedicine has become an indispensable field in biomedical and clinical research, with nanoparticles (NPs) promising to increase the therapeutic efficacy of anticancer drugs. Doxorubicin (DOX) is a commonly used chemotherapeutic drug against OS; however, it causes severe side effects that restrict its clinical applications. Here, we investigated whether combining platinum NPs (PtNPs) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 107 publications
(175 reference statements)
3
46
0
Order By: Relevance
“…These findings indicated that the decreased cell viability and damage caused by the NPs ultimately caused the death of the cells [47]. Others also reported that PtNPs induce cytotoxicity through LDH leakage in cancer cells including A549 lung carcinoma, LNCaP prostate cancer, and OS epithelial (U2OS) cells [17,18,47].…”
Section: Ptnps Induce Cytotoxicity In Thp-1 Cellsmentioning
confidence: 90%
See 4 more Smart Citations
“…These findings indicated that the decreased cell viability and damage caused by the NPs ultimately caused the death of the cells [47]. Others also reported that PtNPs induce cytotoxicity through LDH leakage in cancer cells including A549 lung carcinoma, LNCaP prostate cancer, and OS epithelial (U2OS) cells [17,18,47].…”
Section: Ptnps Induce Cytotoxicity In Thp-1 Cellsmentioning
confidence: 90%
“…This suggested that lycopene reduced Pt ions and formed stable PtNPs. Others also showed that polyvinylpyrrolidone (PVP) [37], apigenin [22], and tangeretin [18] can reduce Pt and stabilize PtNPs. Figure 1B shows that crystalline PtNPs had the features of a Pt face-centered cubic (fcc) phase.…”
Section: Synthesis and Characterization Of Ptnps Using Lycopenementioning
confidence: 99%
See 3 more Smart Citations